2020
DOI: 10.1111/vop.12782
|View full text |Cite
|
Sign up to set email alerts
|

Corneal and scleral permeability of Desmoteplase in different species

Abstract: Objective Intraocular fibrin clots caused by severe uveitis can be a sight‐threatening condition that needs to be resolved quickly and reliably. Intracameral injection of tissue‐plasminogen activator (tPA) is commonly used to resolve intraocular fibrin. However, the drug does not reach fibrinolytic concentrations after topical application. Desmoteplase (DSPA) is a structurally similar but smaller fibrinolytic agent with a higher fibrin selectivity, a longer half‐life, and better biocompatibility compared with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 40 publications
0
2
0
Order By: Relevance
“…Recently, a Russian review mentioned desmoteplase as one of the latest modified variants of a tissue plasminogen activator with a prolonged clearance time, high fibrin-selectivity, and bolus delivery, to be used in acute ischemic stroke treatment [ 45 ]. Moreover, Deborah et al [ 46 ] tested the corneal and scleral permeability of desmoteplase ex vivo both in different animal species and in humans. The rationale behind this study was mainly the documented failure of rtPA to reach fibrinolytic concentrations that are capable of resolving intraocular fibrin.…”
Section: Pharmacokinetics Of Desmoteplasementioning
confidence: 99%
See 1 more Smart Citation
“…Recently, a Russian review mentioned desmoteplase as one of the latest modified variants of a tissue plasminogen activator with a prolonged clearance time, high fibrin-selectivity, and bolus delivery, to be used in acute ischemic stroke treatment [ 45 ]. Moreover, Deborah et al [ 46 ] tested the corneal and scleral permeability of desmoteplase ex vivo both in different animal species and in humans. The rationale behind this study was mainly the documented failure of rtPA to reach fibrinolytic concentrations that are capable of resolving intraocular fibrin.…”
Section: Pharmacokinetics Of Desmoteplasementioning
confidence: 99%
“…Results of this study have reported a higher ability of desmoteplase to permeate both cornea and sclera ex vivo in all the species tested, ranging, respectively, from 0.0 to 16.3 µg/mL and 0.0 to 11.4 µg/mL in rabbits, 0.3 to 5.6 µg/mL and 3.1 to 9.2 µg/mL dogs, 2.1 to 14.9 µg/mL and 4 to 8.7 µg/ml in horses, and 0.6 to 3 µg/mL and 2.9 to 18.1 µg/mL in pigs. Preserved human corneas showed concentrations ranging from 0.07 to 12.9 µg/mL of desmoteplase after diffusion through tissue culture, suggesting that in vivo permeability may be possible [ 46 ].…”
Section: Pharmacokinetics Of Desmoteplasementioning
confidence: 99%